Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L.; Cotti, C.; Cristofolini, G. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract Random Amplified Polymorphic DNA (RAPD) and Inter-Simple Sequence Repeats (ISSR) markers were employed to examine samples from Quercus cerris, Q. suber and Q. crenata in order to test the hypothesis of the hybrid origin of Q. crenata from Q. cerris and Q. suber in a part of its distribution area where the two putative parents do not overlap at present. Leaves from 21 Q. crenata and 37 Q. cerris individual trees were collected at natural sites in northern Italy, where Q. suber is currently lacking; 21 Q. suber and six Q. crenata plants from central Italy were also analysed. Results from Unweighted Pair Group Method with Arithmetic mean (UPGMA) analysis and principal component analysis (PCA) implied that exchange of neutral markers has been considerable between the three species, while differences in morphological characters have remained comparatively stable. The Mantel test indicated low correlation between RAPD- and ISSR-based similarity matrices, showing that the two screening techniques reveal unrelated estimates of genetic relationships. Hybrid indices computed for both markers displayed an intermediate position of Q. crenata individuals between the two putative parents shifted toward Q. cerris. Results from the present study corroborate the hypothesis of a hybrid origin for Q. crenata occurring in northern Italy, and suggest asymmetrical backcrossing with Q. cerris acting as the recurrent parent.
From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: DNA markers; Hybridization; introgression; ISSR; RAPD

Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L.; Cotti, C.; Cristofolini, G. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract Random Amplified Polymorphic DNA (RAPD) and Inter-Simple Sequence Repeats (ISSR) markers were employed to examine samples from Quercus cerris, Q. suber and Q. crenata in order to test the hypothesis of the hybrid origin of Q. crenata from Q. cerris and Q. suber in a part of its distribution area where the two putative parents do not overlap at present. Leaves from 21 Q. crenata and 37 Q. cerris individual trees were collected at natural sites in northern Italy, where Q. suber is currently lacking; 21 Q. suber and six Q. crenata plants from central Italy were also analysed. Results from Unweighted Pair Group Method with Arithmetic mean (UPGMA) analysis and principal component analysis (PCA) implied that exchange of neutral markers has been considerable between the three species, while differences in morphological characters have remained comparatively stable. The Mantel test indicated low correlation between RAPD- and ISSR-based similarity matrices, showing that the two screening techniques reveal unrelated estimates of genetic relationships. Hybrid indices computed for both markers displayed an intermediate position of Q. crenata individuals between the two putative parents shifted toward Q. cerris. Results from the present study corroborate the hypothesis of a hybrid origin for Q. crenata occurring in northern Italy, and suggest asymmetrical backcrossing with Q. cerris acting as the recurrent parent.
From Duplicate 2 (Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - Conte, L; Cotti, C; Cristofolini, G)
Keywords: DNA markers; Hybridization; introgression; ISSR; RAPD

EARLY CHECKING OF GENETIC STABILITY OF CORK OAK SOMATIC EMBRYOS BY AFLP ANALYSIS. - Hornero, J; Martinez, I; CELESTINO, C; Gallego, F J; Torres, V; TORIBIO, M (International Journal of Plant Sciences, 2001)
Early checking of the genetic stability, of tissue culture-derived plants is necessary to obtain all the potential benefits of clonal forestry. Previous work in Quercus suber L. using random amplified polymorphic DNA (RAPD) markers showed no genetic variation among somatic embryos within embryogenic lines of zygotic origin. Genetic fingerprinting based on amplified fragment length polymorphisms (AFLP) allows the direct analysis of variation at the entire DNA level by generating more reproducible markers than RAPDs. To confirm the absence of genetic variation within six embryogenic lines of zygotic origin, six primer pairs were selected out of 48 combinations of primers for revealing up to 512 AFLP markers, 301 of them (58.8%) being polymorphic. The mean number of markers per genotype was 375. Again differences were recorded among embryogenic lines, even between those that arose from half-sib zygotic embryos, but no variation was observed among somatic embryos within embryogenic lines. To check variation in embryogenic lines raised from non-embryonic tissues, somatic embryogenesis was induced in expanding leaves collected from sprouts originating in three mature cork oak. DNA was extracted from leaves and from somatic embryos derived from each tree, and three primer pairs showed 165, 110, and 108 markers per genotype/tree, respectively. In one tree, AFLP patterns generated from leaves and somatic embryos were identical, but variation was detected in samples from the other two trees. Although the level of genetic variation detected in these lines (5.6% and 7.3% of polymorphism, respectively) is lower than that recorded for half sibs of cork oak (25%–31%), its influence on phenotypic variation needs further assessment. [ABSTRACT FROM AUTHOR]
Keywords: AFLP; Cork oak; DNA markers; in vitro culture; Quercus suber; somaclonal variation; Somatic embryogenesis

EARLY CHECKING OF GENETIC STABILITY OF CORK OAK SOMATIC EMBRYOS BY AFLP ANALYSIS. - Hornero, J.; Martinez, I.; Celestino, C.; Gallego, F. J.; Torres, V.; Toribio, M. (International Journal of Plant Sciences, 2001)
Early checking of the genetic stability, of tissue culture-derived plants is necessary to obtain all the potential benefits of clonal forestry. Previous work in Quercus suber L. using random amplified polymorphic DNA (RAPD) markers showed no genetic variation among somatic embryos within embryogenic lines of zygotic origin. Genetic fingerprinting based on amplified fragment length polymorphisms (AFLP) allows the direct analysis of variation at the entire DNA level by generating more reproducible markers than RAPDs. To confirm the absence of genetic variation within six embryogenic lines of zygotic origin, six primer pairs were selected out of 48 combinations of primers for revealing up to 512 AFLP markers, 301 of them (58.8%) being polymorphic. The mean number of markers per genotype was 375. Again differences were recorded among embryogenic lines, even between those that arose from half-sib zygotic embryos, but no variation was observed among somatic embryos within embryogenic lines. To check variation in embryogenic lines raised from non-embryonic tissues, somatic embryogenesis was induced in expanding leaves collected from sprouts originating in three mature cork oak. DNA was extracted from leaves and from somatic embryos derived from each tree, and three primer pairs showed 165, 110, and 108 markers per genotype/tree, respectively. In one tree, AFLP patterns generated from leaves and somatic embryos were identical, but variation was detected in samples from the other two trees. Although the level of genetic variation detected in these lines (5.6% and 7.3% of polymorphism, respectively) is lower than that recorded for half sibs of cork oak (25%–31%), its influence on phenotypic variation needs further assessment. [ABSTRACT FROM AUTHOR]
Keywords: AFLP; Cork oak; DNA markers; in vitro culture; Quercus suber; somaclonal variation; Somatic embryogenesis